Characterization of Efficiency and Mechanisms of Cold Atmospheric Pressure Plasma Decontamination of Seeds for Sprout Production - Waskow, Alexandra; Betschart, Julian; Butscher, Denis; Oberbossel, Gina; Klöti, Denise; Büttner-Mainik, Annette; Adamcik, Jozef; von Rohr, Philipp Rudolf; Schuppler, Markus (Frontiers in Microbiology, 2018)
The consumption of fresh fruit and vegetable products has strongly increased during the past few decades. However, inherent to all minimally processed products is the short shelf life, and the risk of foodborne diseases, which have been increasingly related to such products in many parts of the world. Because of the favorable conditions for the growth of bacteria during the germination of seeds, sprouts are a frequent source for pathogenic bacteria, thus highlighting the need for seed decontamination to reduce the risk of foodborne illness. Consequently, this study focused on cold atmospheric pressure plasma (CAPP) treatment of artificially inoculated seeds in a diffuse coplanar surface barrier discharge to determine the inactivation efficiency for relevant foodborne pathogens and fungal spores. Plasma treatment of seeds resulted in a highly efficient reduction of microorganisms on the seed surface, while preserving the germination properties of seeds, at least for moderate treatment times. To characterize the mechanisms that contribute to microbial inactivation during plasma treatment, an experimental setup was developed to separate ultraviolet light (UV) and other plasma components. The combination of bacterial viability staining with confocal laser scanning microscopy was used to investigate the impact of ozone and other reactive species on the bacterial cells in comparison to UV. Further characterization of the effect of CAPP on bacterial cells by atomic force microscopy imaging of the same Escherichia coli cells before and after treatment revealed an increase in the surface roughness of treated E. coli cells and a decrease in the average height of the cells, which suggests physical damage to the cell envelope. In conclusion, CAPP shows potential for use as a decontamination technology in the production process of sprouts, which may contribute to food safety and prolonged shelf life of the product.